An environmental scan of wellness initiatives and programs at Canadian academic emergency medicine programs: How far have we come?. Issue 6 (November 2020) - Lim, Rodrick; Cameron, Brittany; Gray, Sara; Rang, Louise; Van Aarsen, Kristine
ABSTRACT: Objectives: We sought to conduct a major objective of the Canadian Association of Emergency Physicians (CAEP) Wellness Committee, an environmental scan of the academic emergency medicine programs across the 17 Canadian medical schools. Methods: An 89-question questionnaire was distributed to academic heads or wellness leads. The responses were verified by the lead author to ensure that the questions were answered completely and consistently. Results: While formal wellness programs may exist in varying degrees across the 17 universities, most were found to exist only at local, divisional, or departmental levels. A broad variability of established leadership positions exists. Shift practices varied greatly. In day to day practice, availability for food and debriefing were high and childcare, sleep rooms, and follow-up following critical incidents were low. Sabbaticals existed in the majority of centers. Roughly 50% of departments have gender equity program and annual retreats. Centers report programs for the initiation of leaves (82%), onboarding (64%), and reorientation (94%). Support of health benefits (76%) and pensions (76%) depended on type of appointment and relationship to the university. Fiscal transparency was reported in 53% of programs. Conclusion: Wellness and burnout are critical issues for emergency medicine in Canada. This comprehensive review of wellness programs identifies areas of strength, but also allows identification of areas of improvement for future work. Individual centers can identify common options when developing or expanding their wellness programs.